2010
DOI: 10.1007/s11274-010-0344-4
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of endophyte Pantoea agglomerans YS19 on host rice, with formation of multicellular symplasmata

Abstract: Pantoea agglomerans YS19 is a diazotrophic endophyte isolated from rice (Oryza sativa cv. Yuefu) grown in a temperate-climatic region in west Beijing (China). The colonization of YS19 on host rice was studied in this paper. It was revealed that YS19 colonizes in all the tissues of rice seedlings, including roots (dominantly at elongation regions, lateral root junctions, root hairs and root caps), stems and leaves. More YS19 colonizes in stem and leaves (1.40 9 10 5 CFU mg -1 fresh weight) than that in roots (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 19 publications
3
19
0
Order By: Relevance
“…In addition, extracellular matrices can prevent damage to cells inside a biofilm, brought about by dryness, by increasing water-holding effects (Decho, 2000). Similar to the case of a biofilm, previous electronic microscopic studies on P. agglomerans, including our own, have revealed that a thick matrix of glycoproteins coats the symplasmata (Achouak et al, 1994;Li et al, 2011;Zhang et al, 2010). Moreover, a poor distribution of nutrients induced by cell-aggregating causes the inner cells to metabolize at lowered rates and, however, be more resistant to stresses.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In addition, extracellular matrices can prevent damage to cells inside a biofilm, brought about by dryness, by increasing water-holding effects (Decho, 2000). Similar to the case of a biofilm, previous electronic microscopic studies on P. agglomerans, including our own, have revealed that a thick matrix of glycoproteins coats the symplasmata (Achouak et al, 1994;Li et al, 2011;Zhang et al, 2010). Moreover, a poor distribution of nutrients induced by cell-aggregating causes the inner cells to metabolize at lowered rates and, however, be more resistant to stresses.…”
Section: Discussionmentioning
confidence: 61%
“…Rice diazotrophic endophyte P. agglomerans YS19 was verified to contribute to plant growth (Feng et al, 2006) and its formation of symplasmata is a conducing factor for colonization and stress-resistance (Zhang et al, 2009;Zhang et al, 2010). Formed via aggregation of individual single cells (Duan et al, 2007), symplasmata, in turn, can be induced by adverse environmental stresses, implying their beneficial effects to the bacterial survival adaptation (Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A symplasmatum is a multicellular aggregate structure in which several (at least two) hundreds of individual cells tightly bind together. Zhang et al (2010) reported that even though single cells were used for inoculation, YS19 invaded the plant and colonized in rice almost always as symplasmata, clearly suggesting that these structures are not necessary structures for bacterial invasion but significant for colonization. The main binding components for symplasmata construction are most likely proteins, like SPM43.1.…”
Section: Pantoeamentioning
confidence: 99%
“…Our previous studies had demonstrated that symplasmata are formed by individual cells binding tightly together, independent of solid surfaces [15]. Moreover, the colonization of YS19 in host plant was almost all as symplasmata [16]. Symplasmata not only bestow the strong stress-resistance of YS19 [17,18], but also contribute to the specific adaptation of YS19 in the endophyte-host association [16].…”
Section: Introductionmentioning
confidence: 99%